Cost Stickiness in the local governments of Santa Catarina - Campagnoni, Mariana (2021)
Asymmetric cost behavior took a new approach, starting in 2003, with the emergence of the Cost Stickiness Theory (CST) and, since it is something recent, there are still doubts regarding its application in the public sector. In this sense, this study aims to analyze the behavior of costs in local governments in Santa Catarina, from the cost stickiness perspective. This is an empirical, quantitative, and documentary study that uses the population of 295 municipalities in Santa Catarina during the 20-year period, whose transposition of the analysis model was adapted for the public sector. We grouped the costs in blocks, with the proposition of nine regression models with panel data, of which, eight corroborate the cost stickiness phenomenon. Still, the results indicate similarity with the flypaper phenomenon, typical of the public sector, which uses part of the recipe to calculate the asymmetry, in which of the three types of analyzes performed, the use of the recipe is linked to the one that resulted in the highest sticky. Finally, it offers subsidies for the application of CST to the public sector, even in the case of a typical phenomenon of for-profit entities, and concludes that, with the use of fractional revenue (as well as in the phenomenal flypaper) for local governments of Santa Catarina, the behavior of costs appears to be stickier.